How Much Can a Philosopher Do? - Kerr, Fergus (Modern theology, 2010)
Some philosophers (Stephen Mulhall, Peter Winch, and D.Z. Phillips) complained that in Sources of the Self Charles Taylor allowed his Christian allegiance to "peep through", whereas, as a philosopher, he should have done justice to other views than his own, without taking sides. They would no doubt have protested even more about A Secular Age. Reading these two books in the context of his previous work it becomes hard to accuse Taylor of failing to expound fairly views he opposes, especially regarding British empiricism. Moreover, how disinterested can critical genealogy of religion in the West ever be?